PENGARUH GOOD CORPORATE GOVERNANCE (GCG), PROFITABILITAS, DAN LIKUIDITAS TERHADAP KEPUTUSAN INVESTASI PADA PT BANK MANDIRI (PERSERO) TBK PERIODE 2020 – 2024 - Nugraha, Garnetta Putri; Febrianto, Gustaf Naufan (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This study aims to analyze the influence of good corporate governance (GCG), profitability, and liquidity on investment decisions of PT Bank Mandir (Persero) Tbk during the 2020–2024 period, both partially and simultaneously. The approach used in this study is quantitative, with the population being the annual financial statements of PT Bank Mandiri (Persero) Tbk for the 2020–2024 period officially available on the Indonesia Stock Exchange (IDX). Data sources were obtained from the websites www.idx.co.id and www.bankmandiri.co.id. Data analysis was performed using multiple linear regression using SPSS version 25 software, with a significance level set at 0.05. The research findings indicate that overall, Good Corporate Governance (X?), Profitability (X?), and Liquidity (X?) have a significant influence on Investment Decisions. For further research, it is recommended that the study period be expanded, considering that only two variables show a significant influence. In addition, it is necessary to consider other factors that may also influence investment decisions beyond the variables analyzed in this study.